Global economic crisis of 2008 and its impact on the evolution of the peruvian economy - Sánchez Barraza, Bernardo Javier (2020)
Objective: Determine the impact of the global economy crisis in 2008 on the evolution and process of the economy in Peru during the period 2008-2014. Method: Non-experimental, transversal and retrospective research; the scope is descriptive, correlate, explanatory; quantitative approach, based on measurement, numerical assessment and statistical analysis. Results: It is ruled out that the relationship between GDP growth for the period 2008-2014 and the crisis investigated is null, and according to the results of ARIMA model is found conviction and evidence of a negative relationship between this period and the economy of Peru. Likewise, it is important to underline that in the absence of individual significance, the correspondence has not necessarily been close or direct, but was belatedly shown in the Peruvian economy. Conclusions: Economic events caused a macroeconomic scale impact the global economy, and as Peru is part of it, it will always be positively or negatively affected; however, the impact level will depend on the links and agreements that it can sustain.